2013
DOI: 10.1007/s11769-013-0612-y
|View full text |Cite
|
Sign up to set email alerts
|

A review on rill erosion process and its influencing factors

Abstract: Rills are frequently observed on slope farmlands and rill erosion significantly contributes to sediment yields. This paper focuses on reviewing the various factors affecting rill erosion processes and the threshold conditions of rill initiation. Six factors, including rainfall, runoff, soil, topography, vegetation and tillage system, are discussed. Rill initiation and network are explored. Runoff erosivity and soil erodibility are recognized as two direct factors affecting rill erosion and other types of facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
37
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(39 citation statements)
references
References 91 publications
0
37
0
2
Order By: Relevance
“…In many process-based erosion models, the separation of rill and interrill erosion is of significance to improve the precision on sediment load prediction (Rose et al, 1983;Merritt, 1984;Nearing et al, 1989). Previous research made effort on the division of the erosion processes and quantified the flow hydraulic changes in different stages (Sun et al, 2013). For example, Ellison (1947) tried to divide the water erosion process on slope into four sub-processes: rainfall erosion process, runoff erosion process, raindrop transport process and runoff transport process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many process-based erosion models, the separation of rill and interrill erosion is of significance to improve the precision on sediment load prediction (Rose et al, 1983;Merritt, 1984;Nearing et al, 1989). Previous research made effort on the division of the erosion processes and quantified the flow hydraulic changes in different stages (Sun et al, 2013). For example, Ellison (1947) tried to divide the water erosion process on slope into four sub-processes: rainfall erosion process, runoff erosion process, raindrop transport process and runoff transport process.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors e.g. rainfall, slope gradient, slope length, and soil type, may have significant impacts on erosion processes (Sun et al, 2013;Fang et al, 2014;Zhang et al, 2018). For example, Berger et al (2010) indicated that rainfall intensity has greater effects than slope gradient on rill development and sediment load.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported that rill erosion is directly controlled by combined actions of runoff and soil (Sun et al, 2013). Other factors may have indirect influences on rill erosion by increasing or decreasing the effects of direct factors (Wirtz et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…An understanding of rill erosion processes is not only significant for the soil erosion prevention on sloping croplands but also of importance to soil erosion prediction models (Nearing et al, 1997;Sun et al, 2013). Therefore, a laboratory study was conducted under controlled experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, to control soil erosion, it is important to identify the most vulnerable soils and land uses. In regions where water erosion is the dominant, studies on individual slope scale have proven fruitful (Kinnell, 2013;Li et al, 2009;Sun et al, 2013). However, only limited information is available for erosion and sediment characteristics on larger scales, such as catchments and whole river systems.…”
Section: Introductionmentioning
confidence: 99%